Crecimiento y mortalidad de la concha nácar Pteria sterna en bancos silvestres de Baja California Sur, México - Wright-López, Humberto (2009)
The Gulf of California nacre shell Pteria sterna is an important marine resource in Mexico, and the main species for “half” and round pearl production in the American continent. Wild spat can only be extracted legally for research or culture activities. This study calculates growth and mortality parameters for wild stocks in the eastern coast of Southern Baja California. Height’s data (353 dorso-ventral measurements) were taken from 1997 to 1999 at Santa Rosalía, Mulegé and Loreto Bay coast. The maximum length was estimated at 130.35 mm (124.22-136.48 mm, p>0.95). The length frequency data were set in a “virtual year”. Seasonal von Bertalanffy growth parameters were calculated in the ELEFAN I routine, the values are: L∞ = 156.02 mm, k = 0.48 year-1, t0 = -0.216 years, C = 0.43, WP = 0.73. and ts = 0.5. The growth performance index was Φ’ = 4.068. The total mortality was calculated from length-converted catch curve Z = 3.34 year-1. The length-weight relationship was fixed for the equation W = 0.000756 * L(i)2.7075 (r2 = 0.90, n = 233). The growth parameters values in experi-mental repopulation conditions are quite different, in contrast with the growth estimated in wild stocks oysters. The value of total mortality is similar to the estimations for Pinctada fucata populations from the Red Sea and P. radiata from the Mediterranean Sea.